PENGARUH AKTIVITAS PERUSAHAAN TERHADAP PROFITABILITAS DAN PELUANG INVESTASI PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG GO-PUBLIC DI INDONESIA - Jonathan, LCA Robin; Militina, Theresia (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the effect of company activity that projected in four variables, i.e., Total Asset Turn Over (TATO), Inventory Turn Over (ITO), Fixed Asset Turn Over (FATO), and Working Capital Turn Over (WCTO) on profitability (Return on Asset/ROA) and investment opportunity in the public companies in Indonesia incorporated in the consumer goods industry sector during the period of 2013-2015. The research data were sourced from the company financial reports taken from 37 companies as the research sample that consist of the following industry sub-sectors: food and beverage (17 issuers), cigarettes/tobacco (4 issuers), pharmaceuticals (9 issuers), cosmetics and household needs (4 issuers), and household appliances (3 issuers). Data were analyzed using multiple linear regression and path analysis. The results showed that simultaneously company activity has a significant effect on ROA and ROA significantly mediates the effect of TATO on investment opportunity. However, ITO, FATO, and WCTO have no significant effects on ROA or investment opportunity.